2022
DOI: 10.53471/bahce.1019023
|View full text |Cite
|
Sign up to set email alerts
|

Production of Stone Fruit in Turkey and Evaluation of Competitiveness Power on Export

Abstract: Meyve, besin değeri açısından yüksek ve glisemik indeksi düşük olduğundan tercih edilen besinlerin başında gelmektedir. Türkiye’de meyvecilik sektörü, iklim koşulları sayesinde üretim ve ihracat açısından dünyada önde gelen ülkelerden biridir. Meyve çeşitleri yumuşak çekirdekli, sert çekirdekli, sert kabuklu, üzümsü ile turunçgil ve diğer meyve türleri olmak üzere beşe ayrılmaktadır. Bu çalışmada, literatürde sert çekirdekli meyve kategorisinde bulunan kiraz, vişne, kayısı, erik ve şeftali-nektarin meyvelerini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Turkiye's RSCA index values in 24 product groups are more prominent than for its trading partners, as Erkan and Sarıcoban (2014), Topcu and Sarigul (2015), Sahin (2016b), Bashimov (2017), Bakkalci (2018), Kathuria (2018), Keskingoz (2018), Keskingoz vd. ( 2020), Baskol and Bektas (2021), Kılıcarslan (2021), Duru et al (2022), Topcu (2022), Yıldız (2022) and Kantur and Turkekul (2023) demonstrated before. This indicates that Turkiye has higher export potential in those products due to them.…”
Section: Discussionmentioning
confidence: 96%
“…Turkiye's RSCA index values in 24 product groups are more prominent than for its trading partners, as Erkan and Sarıcoban (2014), Topcu and Sarigul (2015), Sahin (2016b), Bashimov (2017), Bakkalci (2018), Kathuria (2018), Keskingoz (2018), Keskingoz vd. ( 2020), Baskol and Bektas (2021), Kılıcarslan (2021), Duru et al (2022), Topcu (2022), Yıldız (2022) and Kantur and Turkekul (2023) demonstrated before. This indicates that Turkiye has higher export potential in those products due to them.…”
Section: Discussionmentioning
confidence: 96%